Enhancing Flame Retardancy and Smoke Suppression in Epoxy Resin Composites with Sulfur–Phosphorous Reactive Flame Retardant - Xulong Ma; Ni Kang; Yonghang Zhang; Yang Min; Jianhua Yang; Daming Ban; Wei Zhao (Molecules, 2023)
The presence of massive amounts of toxic volatiles and smoke during combustion is a very serious problem facing epoxy resin (EP) composites. Therefore, flame retardants (FRs) can simultaneously enhance flame retardancy and reduce the release of smoke and fatal gases. Herein, a novel sulfur–phosphorous reactive flame retardant (SPMS) was synthesized for epoxy resin. The high efficiency of smoke suppression and flame retardancy of the EP/SPMS-APP hybrid was investigated using a cone calorimeter, a vertical burning test, and limited oxygen index measurements. Compared with those of pure EP, the composite with 20 wt% SPMS-APP reduced the peak heat release rate (pHRR), the peak smoke production rate (SPR), and total smoke production rate (TSR) by 82%, 94%, and 84%, respectively. The results showed a remarkable suppressed effect of alleviating the fire hazard of EP using a sulfur–phosphorus flame retardant.